STALLED FERTILITY DECLINE IN EAST NUSA TENGGARA, INDONESIA, 2002-2017: UNDERSTANDING ITS DETERMINANTS - Melianus Mesakh Taebenu (Jurnal Kependudukan Indonesia, 2020)
Indonesia is one of the countries that has been relatively successful in completing a fertility transition. However, provincial differences in fertility still exist, with East Nusa Tenggara (Nusa Tenggara Timur – NTT) having the highest Total Fertility Rate in 2017 (TFR, 3.4 births per woman). By employing a document analysis method, this study explores the indirect and direct determinants of the stalled fertility decline in NTT. It is revealed that all indirect determinants of fertility –culture, socioeconomics, and governance– have shaped women's persistent fertility behaviour in NTT. Meanwhile, among three direct determinants of fertility –marriage, contraception, and postpartum infecundability–, contraception is the only determinant that has been responsible for the stall of fertility transition in this province. These findings suggest that to foster the fertility decline in NTT, the government plays an essential role in boosting the provision of contraception, information and education, and providing incentives for having fewer children.